Bola Tangkup: A Media to Stimulate Gross Motor Skills’ Children with Visual Impairment - Kurniadi, Andi; Ciptono, Ciptono (Indonesian Journal of Early Childhood Education Studies, 2015)
This study aims to determine how the development of media Ã¢â‚¬Å“bola tangkupÃ¢â‚¬Â and test the effectiveness of the media Ã¢â‚¬Å“bola tangkupÃ¢â‚¬Â sphere to stimulate the gross motor ability of blind children. The method used the Research and Development (R & D) but is more focused on the development of procedural models by Borg & Gall simplified. The development phase of this research begins with an analysis of potential problems, requirements analysis, product design, design validation, and applied it, then conducted tests gross motor ability of children. Data was analyzed using descriptive qualitative descriptive analysis of the needs and the percentage of the results of expert validation and testing of the product. Design validation results showed that the media developed has met the eligibility test media expert and skilled children with special needs and can be used for media learning gross motor stimulation. Media expert validation results expressed strongly agree with 81.12% and the percentage of children with special needs experts strongly agreed with a percentage of 90.59%. The trial results demonstrate the ability of sound ball an average percentage of 39.58% and ability after treatment using Ã¢â‚¬Å“bolatangkupÃ¢â‚¬Â an average percentage of 73.21%. It can be concluded that the use of media Ã¢â‚¬Å“bolatangkupÃ¢â‚¬Â is more effective than using the ball sounds. Besides media Ã¢â‚¬Å“bolatangkupÃ¢â‚¬Â can be used as a step to introduction characteristics braille is using the seeds of the more interesting and fun for blind children. Research needs to be conducted extensive testing in order to improve media development Ã¢â‚¬Å“bolatangkupÃ¢â‚¬Â of higher quality.How to citeKurniadi, A. & Ciptono. (2015). Bola Tangkup: A Media to Stimulate Gross Motor SkillsÃ¢â‚¬â„¢ Children with Visual Impairment. Indonesian Journal of Early Childhood Education Studies, 4(2), 86-89. doi:10.15294/ijeces.v4i2.9461DOI 10.15294/ijeces.v4i2.9461